Analisis Pengaruh Tekstur Dan Stuktur Tanah Terhadap Kemampuan Menyimpan Air Dilahan Pertanian Datar Rendah - Helmin Parida Zebua; Trisna Sari Mendrofa; Inca Paskahlia Waruwu; Frans Zefrindo Two Waruwu; Irvan Havis Gea; Jufrilinus Waruwu (CV. SINAR HOWUHOWU, 2026)
The soil’s ability to store water is one of the key factors determining agricultural productivity, particularly in lowland areas that frequently experience water saturation. This study aimed to examine the effects of soil texture and structure on the soil’s water-holding capacity. Soil samples were collected from several points in lowland areas and subsequently analyzed in the laboratory using the pipette method to determine soil texture, morphological observations to assess soil structure, and the gravimetric method to measure water-holding capacity. The results showed that fine-textured soils, such as clay, have a higher water-holding capacity compared to coarse-textured soils, such as sand. Soil structures that are granular and stable enhance soil porosity and enable water to be retained for a longer period. The combination of clay texture and granular structure resulted in the most optimal soil water-holding capacity. Therefore, soil physical conditions, particularly texture and structure, play a crucial role in maintaining soil water balance. Soil management practices involving the addition of organic matter and appropriate tillage are essential measures to improve soil water-holding capacity and support sustainable agriculture in lowland areas.